Neoadjuvant Chemotherapy for Early Stage Cervical Cancer - TADJOEDIN, HILMAN (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43601513/Neoadjuvant-Chemotherapy-for-Early-Stage-Cervical-Cancer